Localization in multipath environments - Seow, Chee Kiat (2009)
This thesis focuses on the design of localization schemes and algorithms which work in multipath environments. Traditionally, conventional localization schemes work based on the assumption that the reference devices (RDs) are always in Line-of-Sight (LOS) with the mobile device (MD) to locate the MD. However, this assumption will not hold in multipath environment as the RDs may be in Non-Line-of-Sight (NLOS) with the MD and causes erroneous estimation in the MD location. To resolve such inaccuracy, the conventional localization schemes are usually coupled with mitigation schemes to reduce such NLOS error.In this thesis, we focuses on the design of localization schemes with the intent that they work without any mitigation techniques and yet able to localize the MD in the multipath environment where the existence of LOS is not guaranteed. Firstly, a bi-directional localization scheme that detects LOS paths and leverages on their Time of Arrival (TOA) and Angle of Arrival (AOA) measurement data at both the RDs and MD in a general multipath environment was proposed. It was compared with the conventional localization schemes that coupled with their mitigation schemes. Another bi-directional localization scheme with the enhancement of LOS paths' measurement data was designed and tested out in a real multipath environment.Next, in order to utilize the non line of sight (NLOS) path that undergoes one bound scattering phenomenon, a bidirectional NLOS localization scheme was designed. As such, both the LOS or NLOS paths can be used for localization. Paths that undergo multiple bound scattering phenomenons were successfully discarded using the devised multipath detection scheme. This NLOS localization scheme was validated in a real multipath environment.Finally, a unidirectional localization scheme that uses only the TOA and AOA measurement data at the RDs was proposed. It was being validated in a parallel/perpendicular aligned scatterers' multipath environment. Furthermore, a unidirectional localization scheme that provides an enhancement to the LOS path was designed. The scheme's robustness to non parallel/perpendicular aligned scatterer was investigated.It is worthy to note that in general, all our proposed localization schemes are not only able to localize the MD using just one RD but also able to achieve better localization accuracy than the conventional localization schemes.